Marine Anti-inflammatory Agents - Talero, Elena (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Acute inflammation is a highly regulated process, and its dysregulation can lead to the development of a chronic inflammatory state which is believed to play a main role in the pathogenesis of many diseases, including cancer. In recent years, the need to find new anti-inflammatory molecules has raised the scientific community´s interest for marine natural products. In this regard, the marine environment represents a source for isolating a wealth of bioactive compounds. In this Special Issue, the reported products have been obtained from microalgae, sea cucumber, octopus, squid, red alga-derived fungus, cnidarians, hard-shelled mussel, and sponges.